Business Process Reengineering In The Light Of Strategic Direction In Field Study Of Sample Of High Level In The Ministry Of Oil - محمد, نسرين جاسم; خلف, زينب ابو علي (Journal of Economics and Administrative Sciences, 2017)
The current research aims to determine the extent of the impact of the strategic direction to the  business process reengineering, in the Office of the Ministry of Oil To reach that goal was a sample of community research study consisted (50) members of the senior leadership represent the problem in organization researched in the ambiguity of the strategic direction of knowledge of the compatibility of the strategic direction with Business Process Reengineering and   used questionnaire, interview and  observation to obtain the information needed to search was addressing data by the statistical system spss percentage  and the arithmetic mean, standard deviation and coefficient of variation .The research found a set of conclusions, including that there is a link and the impact of the strategic direction and business process reengineering relationship suffers organization researched the ambiguity in the strategic direction qualification for leadership and low, where most of them were bachelor degree holders as well as the decrease in the number of young leaders to fill leadership positions and the existence of an organizational structure pyramid complex is reflected in the slow pace of proceedings by the recommended current  research need to formulate strategic direction of the vision, mission and goals as an actor that includes strategic direction has can application of strategic business process reengineering and provide an opportunity for groups of young woman in leadership positions and higher education and hold radical changes to the human and organizational level and the technological and operational in the surveyed organization